Evaluating Satisfaction Of International Students At Tehran University Of Medical Sciences (TUMS) - Ali Arab Kheradmand; Enayatollah Shabani; Tannaz Azadi (پیاورد سلامت, 2015)
Background and Aim: Today universities admit International Students as well as national students. Tehran University of Medical Sciences has been also started admitting International Students in regards of its Internationalization aims. Student’s satisfaction is of high importance in order to gain the given goals. The purpose of this study was to evaluate the satisfaction of International students of TUMS. Materials and Methods: This was a descriptive study. The target group was international students of TUMS, the participants were selected through availability sampling. The research instrument was researcher-made questionnaire which the reliability calculated as 0.97 by Chronbach’s alpha. The data was analysied by Microsoft Excell version 2010. Results: The overall satisfaction of the students was 70% (satisfied and completely satisfied) while the overall dissatisfaction was 10% (dissatisfied and completely dissatisfied). Conclusion: Given satisfaction of more than half of the International students, TUMS has performed reasonably. Based on the results obtained in this research the university may pay attention to the fields reported as dissatisfied.